Numerical Calculation Analysis of the Structural Stability of Cemented Fill under Different Cement-Sand Ratios and Concentration Conditions - Kang Zhao; Qiang Li; Yajing Yan; Keping Zhou; Shuijie Gu; Shengtang Zhu (Advances in Civil Engineering)
The effect of lime-sand ratio and slurry concentration on the mechanical properties of backfills is important. To achieve green and high-efficiency mining, accurately determining the optimum ratio of cemented tailings for certain tungsten tailings and ensuring the safety and stability of the mine stope structure are important. The cement-sand ratios used in this research were 1 : 6 and 1 : 8. The mechanical properties were evaluated by using 68%, 72%, and 78% of tailing cemented filling materials. The corresponding physical and mechanical parameters were obtained through uniaxial compression, splitting, and shearing mechanical experiments on the backfill specimens. FLAC3D was used to investigate the mechanical properties of cement-filled pillars and the stability of supporting surrounding rocks on the basis of the mine’s current room pillar structure size parameters and mining sequence. The key factors that affect the stability of the goaf were analyzed by evaluating the plastic zone area of the stope, maximum and minimum principal stresses, and displacement change. The structural characteristics of stope structures and changes of rock mass damage were obtained under different cement-tailing ratios and concentrations. A cemented backfill with a cement-tailing ratio of 1 : 8 and a concentration of 68% was selected as the best solution for the mine in terms of safety and economic considerations.